Variability of Physicochemical Database and Trypsin Inhibitory Activity of Komak (Lablab purpureus (L.) Sweet) Beans with Distinct Colors - Werdiningsih, Wiharyani; Utami, Tyas; Rahayu, Endang Sutriswati; Setyaningsih, Widiastuti (Trends in Sciences, 2024)
Komak (Lablab purpureus (L.) sweet) is a highly productive plant used for sustainable cultivation. However, beans are currently underutilized. A complete database including physicochemical characteristics is important for developing new foods derived from komak beans. This study aimed to determine the physical (weight, dimensions and color) and chemical (macromolecules, amino acids, sugars, minerals, phytic acid, tannin and volatile compounds) profiles, as well as the trypsin inhibitory activity of different varieties of komak beans, viz. white and black beans. The levels of the studied parameters differed significantly (p < 0.05) between the beans. However, the common profile of komak beans was characterized by a moderate level of protein (26 %), high carbohydrate (66 %) and low fat (2 %), with a weight ranging from 25 to 45 g and low anti-nutritional factor expressed as trypsin inhibitory activity (2 TIU/mg). Additionally, analytical results using HS-SPME-GC/MS revealed that 1-octen-3-ol and benzyl alcohol were the main unpleasant volatile compounds produced upon heating beans. The major mineral compound in black beans is potassium, whereas the white variety contains higher amounts of magnesium, calcium and iron. Interestingly, both beans provided favorable compounds contributing to the umami taste, as the most dominant amino acids were glutamic and aspartic acids. Finally, as white beans were lower in antinutritive compounds (phytic acid and tannin), this measure may encourage further studies to expand the development of this variety to promote underutilized beans as alternative food sources. HIGHLIGHTS Komak is a productive and sustainable crop with underexploited beans The 2 types of komak beans were medium-sized, containing moderate protein, high carbohydrates, low fat and low trypsin inhibitory activity 1-Octen-3-ol and benzyl alcohol were the major unpleasant volatile compounds produced by the beans White beans have high magnesium, calcium and iron; black beans are primarily rich in potassium White beans had less anti-nutritive phytic acid and tannin than black beans GRAPHICAL ABSTRACT